Ustekinumab for ulcerative colitis: a nationwide real-life observational cohort study - Molander, Pauliina; af Björkesten, Clas-Göran; Henricson, Hans; Koskela, Ritva; Nuutinen, Heikki; Käräjämäki, Aki; Tillonen, Jyrki; Tauriainen, Milla-Maria; Kellokumpu, Mikko; Eronen, Heli; Suhonen, Ulla-Maija; Vihriälä, Ilkka; et al. (Ovid Technologies (Wolters Kluwer Health), 2025)
Objective This nationwide retrospective chart review study assessed ustekinumab treatment persistence and clinical outcomes of ustekinumab treatment in Finnish patients with ulcerative colitis in a real-world setting.
Methods Data was collected retrospectively until April 2022 from patient charts for all patients with ulcerative colitis who started ustekinumab between September 2019 and December 2021 in 16 Finnish inflammatory bowel disease centers. The primary outcomes were persistence on ustekinumab and clinical remission/steroid-free clinical remission, defined as partial Mayo score <3 and a combined stool frequency and rectal bleeding subscore of ≤1 at 16 weeks and 1 year.
Results The study included 221 patients with an average follow-up of 14.7 months and a median disease duration of 5.5 years. Disease status was endoscopically evaluated as severely active in more than 91% of the patients at baseline. Treatment persistence was 87% at 16 weeks and 63% at 1 year. The clinical/steroid-free remission rate was 49%/46% at 16 weeks and 68%/62% at 52 weeks, respectively. Decreases in fecal calprotectin and partial Mayo scores were observed. Concomitant corticosteroid use decreased from 60% at baseline to 28% at 16 weeks and to 16% at 1 year during ustekinumab maintenance therapy. Antibodies to ustekinumab were detected in very few patients (<5, <21%), and discontinuation was observed due to adverse effects even less frequently (<5, <6%).
Conclusion This real-world study demonstrated that ustekinumab has sustained efficacy in the treatment of ulcerative colitis in a real-world setting.